Improved hybrid modular multilevel converters with dc short-circuit fault ride-through capacity - Yuhang Lei; Gangquan Si; Jianwei Zhu; Yanbing Zhang (The Journal of Engineering, 2018)
Modular multilevel converter (MMC) has become a promising converter alternative for transmission voltage-source converter high-voltage direct current applications. The main issue and challenge of MMC is how to handle the dc short-circuit fault. Based on the half-bridge MMC, this study proposed an improved hybrid MMC topology which has the dc faults ride-through capability and requires less switching devices contrast with the present hybrid topology. The improved hybrid topology consists of m half-bridge submodules and n modified half-bridge sub-modules (e-RBSM) which consists of an insulated gate bipolar transistor (IGBT), two reverse blocking IGBTs (RB-IGBTs), two diodes and a resistance. The required number of e-RBSM n is deduced according to the dc short-circuit fault ride-through requirement. Moreover, the analysis of the fault current blocking mechanism and electrical stress of the power switches is made in detail. Furthermore, the improved topology allows all RB-IGBTs not to conduct simultaneously by employing the parallel circuit including a diode and a resistance, therefore, it reduces the requirement of trigger pules operation. Simulation results on PSCAD/EMTDC verify the efficiency of the proposed topology and strategy.